Nilai Pendidikan Karakter dalam Novel Mitra Sejati Karya Tulus Stp Sebagai Bahan Ajar Pembangun Profil Pelajar Pancasila dalam Pembelajaran Bahasa Jawa - Ningrum, Andriana Dwi; Sunarya, Sunarya; Werdiningsih, Yuli Kurniati (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2022)
This study aims to describe the value of character education in the novel Mitra Sejati Karya Tulus Stp as a teaching material to build a profile of Pancasila students in learning Javanese.This study uses qualitative research methods because the data are in the form of phrases, clauses, sentences, and discourses. The data source used is the novel Mitra Sejati by Tulus Setiyadi. Data collection techniques are in the form of documentation studies consisting of reading techniques and note-taking techniques. Data analysis techniques used in the form of data reduction, data display and data verification.The results of this study indicate that there are several values of character education that are relevant to the Javanese language curriculum at the junior high school level. First, character values respect and appreciate the teachings of the religion adopted. Second, the value of the character of responsibility. The third, the value of caring character. Then there is the value of character education as a teaching material to build the profile of Pancasila students in Javanese language learning, namely the values of respecting and living the teachings of the religion adopted, as well as responsibility.